Potency of Rhodotorula minuta as Plant Growth Promoter on Red Chili Plant Infected by Colletotrichum acutatum - Sri Hartati; Linda Tarina; Endah Yulia; Luciana Djaya (CROPSAVER, 2019)
Some yeast species were reported to have the ability to promote plant growth. Rhodotorula minuta is a yeast species that has the potency as biocontrol agent. This research was objected to evaluate the potency of R. minuta in promoting the growth of red chilli infected by Colletotrichum acutatum. The experiment was carried out at the Laboratory of Plant Protection Biotechnology and Green House of Ciparanje Experiment Station, Faculty of Agriculture, Universitas Padjadjaran. The experiment was arranged in the randomized completely block design with 9 treatments and 5 replications. The treatments were infestation of R. minuta and inoculation of C. acutatum on 5, 7, and 10 days after replanting, and a positive control with no R. minuta infestation but inoculated with the pathogen and a negative control without R. minuta infestation nor pathogen inoculation. Results of the experiment showed that the effectiveness of the treatments with R. minuta on the increase of the chilli plant height was 3.78-17.90%, leaf number was 4.09-15.19%, and dry weight of the biomass was 0.14-0.58%. This results indicated that treatments with R. minuta were able to promote the growth of chilli plants.